Pilgrims and Sacred Sites in China - Naquin, Susan; Y|, Ch|n-Fang (Berkeley, CA : University of California Press, 2020)
Until now, China has been scarcely represented in the burgeoning comparative literature on pilgrimage. This volume remedies that omission, discussing the interaction between pilgrims and sacred sites from the tenth century to the present. From the perspectives of literature, art, history, religion, politics, and anthropology, the essays focus on China's most famous pilgrimage mountains as well as lesser known sites.
Frontmatter -- CONTENTS -- ILLUSTRATIONS -- ACKNOWLEDGMENTS -- INTRODUCTION: PILGRIMAGE IN CHINA -- ONE. Women Pilgrims to T'ai Shan: Some Pages from a Seventeenth-Century Novel -- TWO. An Ambivalent Pilgrim to T'ai Shan in the Seventeenth Century -- THREE. Chang Shang-ying on Wu-t'ai Shan -- FOUR. Relics and Flesh Bodies: The Creation of Ch'an Pilgrimage Sites -- FIVE. P'u-t'o Shan: Pilgrimage and the Creation of the Chinese Potalaka -- SIX. Huang Shan Paintings as Pilgrimage Pictures -- SEVEN. The Pilgrimage to Wu-tang Shan -- EIGHT. The Peking Pilgrimage to Miao-feng Shan: Religious Organizations and Sacred Site -- NINE. Reading the Chairman Mao Memorial Hall in Peking: The Tribulations of the Implied Pilgrim -- CONTRIBUTORS -- GLOSSARY-INDEX
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 01. Okt 2020).
JSTOR
Keywords: Buddhist pilgrims and pilgrimages -- China -- Congresses; Pilgrims and pilgrimages -- China -- Congresses; HISTORY -- Asia -- General; HISTORY / Asia / General; Buddhist pilgrims and pilgrimages; Pilgrims and pilgrimages; China; Conference papers and proceedings